Boeotian Accentuation in the Ancient Editions of Boeotian Poetry. - Vessella, Carlo (Mnemosyne, 2016)
This paper argues that the papyri containing Boeotian poetry provide no evidence in support of a dialect-specific accentuation of Boeotian. Lectional signs on the extant papyri of Boeotian poetry follow for the most part the current accentuation practice of the 2nd and 3rd centuries CE, equating Boeotian to the standard of Attic and the Koine: in their editions of Boeotian texts modern editors should refrain from introducing accentuation that does not follow that standard.